Microstructural Analysis From X-Ray CT Images of the Brae Formation Sandstone, North Sea - Thomson, Paul-Ross; Ellis, Rory; Chiarella, Domenico; Hier-Majumder, Saswata (Frontiers in Earth Science, 2020)
During deposition and subsequent diagenesis, reservoir rocks develop sediment texture and cement phases are formed during the precipitation of secondary minerals such as microcrystalline quartz, calcite and clay fibrous over-growths that contain secondary porosity. The grain size distribution and presence of secondary microporous material can influence the reservoir porosity and permeability. Using 3D X-ray microtomographic images we analyze the grains and pore space in Brae Formation sandstones from the South Viking Graben in the North Sea. The samplesderived from two cored wells (16/7b-20 and 16/7b-23), and located within the depth interval between 4040 m and 4064 m-display mean grain sizes between 315-524 microns (1.78-1.05 φ units), classifying them as predominantly medium-grained sands, with moderate to well sorting (0.51-0.7 φ units). From our models we calculate the upper and lower bounds of the micropores on the pore connectivity and permeability. Our samples show total porosities between 10 and 18% of which 6 and 13% are effective, leading to a permeability range between 1 and 400 mD through the effective macropore network. We found that the fraction of effective porosity and effective permeability shows a nonlinear reduction with increase in microporous cement volume fraction. Above a threshold cement volume of approximately 5.5% the effective pore network is disconnected and percolation is no longer possible. Based on our observations and modeling results we propose that cement precipitation can be a positive consequence of mineral trapping from sequestered CO2 , which can be important for reducing reservoir quality and ensuring efficient long term storage.